(untitled) (Balneo and PRM Research Journal, 2024)
Sleep plays a crucial role in physical and mental well-being, being a fundamental component of the body’s natural rehabilitation and recovery process. Adequate sleep not only facilitates tissue repair but also enhances cognitive function and mood. For those undergoing physical rehabilitation or recovering from injuries, prioritizing restorative sleep is indispensable, as it accelerates healing processes. Recent studies explore innovative technologies like rocking beds to enhance sleep quality. While anecdotal evidence suggests benefits, scientific literature on rocking beds remains limited. This narrative review examines the impact of rocking movements on sleep quality and memory processes. Studies suggest potential benefits, such as increased duration of deep sleep and enhanced sleep quality. However, conflicting findings indicate the need for further research. Keywords: Sleep Quality, Rocking Movements, Rehabilitation, Sleep Environment